Ground Penetrating Radar Theory and Applications. - Jol, H. M. (Harry M.) (Burlington : Elsevier, 2009)
Ground penetrating radar (GPR) is a rapidly growing field that has seen tremendous progress in the development of theory, technique, technology, and range of applications over the past 15-20 years. GPR is increasingly being used by a variety of scientists, researchers, engineers, consultants, and university students from many disciplines. The diversity of GPR applications includes a variety of areas such as the study of groundwater contamination, geotechnical engineering, sedimentology, glaciology, and archaeology. This breadth of usage has lead to GPR?s rapid development and pre-eminence in g.
Chapter 7 The Contribution of Ground Penetrating Radar to Water Resource ResearchChapter 8 Contaminant Mapping; Part III Earth Science Applications; Chapter 9 Ground Penetrating Radar in Aeolian Dune Sands; Chapter 10 Coastal Environments; Chapter 11 Advances in Fluvial Sedimentology using GPR; Chapter 12 Glaciers and Ice Sheets; Part IV Engineering and Societal Applications; Chapter 13 NDT Transportation; Chapter 14 Landmine and Unexploded Ordnance Detection and Classif.
Print version record.
Keywords: Ground penetrating radar; Electronic books